A Juridical Study of the Death Penalty for Premeditated Murder in the Perspective of Indonesian Criminal Law Reform - Evelin Nur Agusta; Pujiyono Pujiyono; Nabitatus Sa'adah; Aista Wisnu Putra (Jurnal Pembangunan Hukum Indonesia, 2025)
One of the most serious crimes is premeditated murder because it is carried out with deliberate planning and conscious thought of the loss of the victim's life. The definition and specifications of the planning aspect in premeditated murder are not regulated in the Criminal Code. The deterrent effect of the death penalty in premeditated murder must be considered by the judge very carefully, because the death penalty is irreversible . In addition, in terms of the implementation of the death penalty which still reaps protests from human rights activists. This paper aims to re-describe the relevance and urgency of the death penalty in terms of punishment for perpetrators of premeditated murder. The type of research used in this writing is a type of doctrinal research, using an analytical approach method to the norms behind the text of the legislation, both legally and philosophically. This study produces an analysis of the element of planning in the Criminal Code and the conclusion is that there are no clear details about the element of "planning" in Article 34 of the old Criminal Code or Article 459 of the new Criminal Code.